An empirical investigation of the applicability of the debt overhang hypothesis in Zimbabwe - Masere, Victoria; Chikaza, Z (IUP Publications, 2022)
This study empirically tests the applicability of the debt overhang hypothesis in Zimbabwe using time series data covering the period 1980 to 2009 by analyzing the relationship between economic growth and external debt (termed as direct debt hypothesis), using cointegration analysis as well as the causal relationship between external debt and investment (termed as indirect debt hypothesis), and also using Granger causality tests. Regression results from the growth model indicate the presence of a debt overhang in Zimbabwe as evident from the negative relationship between external debt and economic growth, while those from the external debt investment model show the absence of an indirect debt overhang.